In vitro germination of Dendrocalamus strictus (Rosb.) Nees seeds - Yudith García-Ramírez; Marisol Freire-Seijo; Marisol Tejeda; Maritza Reyes (Biotecnología Vegetal, 2007)
The availability of D. strictus seeds is affected by the length and erratic flowering cycle of the species. These seeds also retain their germination only for short periods of time. The tissue culture offers a fast and reliable way for the propagation using in vitro seed germinated as initial plant material. This research was conducted with the objective of to germinate in vitro D. strictus seeds. The effect of different concentrations of sodium hypochlorite (NaClO) (3.0, 5.0 and 7.0%) and time for seed disinfection (20 and 30 min) were determined. It was evaluated the number of germinated seeds and free of microbial contaminants after 10 days of culture. The results showed that the method of disinfection which sodium hypochlorite 3.0% for 30 minutes was the best for in vitro germination of Dendrocalamus strictus (Rosb.) Nees seeds. Key words: bamboos, disinfection, sodium hypochlorite, tissue culture